Development Of Learning Video: Mangroves And Phytoplankton In Batu Ampar, West Kalimantan - Daningsih, Entin; Ramadhan, Ramadhan; Da Costa, Yuliana Ovan (BIOEDUSCIENCE, 2023)
Background: Mangrove forests experience rapid destruction; nonetheless, Indonesia has the widest mangrove area in the world. Conservation efforts must involve all parties, including education. This research was to develop learning video media about mangroves and phytoplankton. Methods: The method used was development research with a 4D model (defined, designed, developed, and disseminated) to develop a video containing the environmental conditions of mangroves and their unique roots in Batu Ampar. The video was evaluated by validators using a questionnaire as a research instrument. The assessment used a Likert scale. The video was also tested limitedly. Data were analyzed to calculate the content validity ratio (CVR) and the percentage category of students as respondents. Results: Learning video media about mangroves and phytoplankton in Batu Ampar obtained CVR 1,00 and categorized it as valid and suitable for learning media. Based on the limited test, students showed that both cognitive and affective were very good, but psychomotor was only a good category.